Yes Means Yes, No Means No, and Closing the Door Means Sure? Exploring Internal and External Cues of Consent to Sex Among Young Adults in Aotearoa New Zealand - Jackman, Chloe (Auckland University of Technology, 2024)
As Aotearoa New Zealand endeavours to eliminate sexual violence through its national strategy, Te Aorerekura, we need to direct more attention towards contemporary sex and consent culture. However, to develop relevant policy, it is imperative that there is psychological insight into how consent is understood within the sociocultural context. The current study aimed to explore how young adults consent to sex by assessing feelings that influenced the decision to engage in a recent sexual interaction and how/if they communicated this willingness through behaviours. An online questionnaire that included the Internal Consent Scale and External Consent Scale by Jozkowski et al. (2014) was completed by 509 young adults. Preliminary analyses indicated group differences: those in a relationship were more likely to experience feelings of consent and use communication behaviours than single individuals; Rainbow young adults were more likely to use verbal cues whereas heterosexual young adults were more likely to suggest sex “just happened”; and males reported using more behaviours to convey consent than females. The main analyses involved performing exploratory factor analyses. The Internal Consent Scale was refined from the original 25-item, five factor structure to a two-factor solution: Factor 1 was comprised of seven items pertaining to cognitive perceptions associated with affirming willingness and Factor 2 was composed of seven items posited to represent physiological arousal. Although the current study also obtained a five-factor solution for the External Consent Scale, the underlying structure did not replicate, thus raising concern about the subscales. Overall, these findings provide an important contribution to the emerging literature regarding cues of consent which is imperative for the prevention of sexual violence.